COASTAL RESOURCE DEVELOPMENT IN MALAYSIA: IS THERE A NEED FOR SUSTAINABLE MANGROVE FOREST MANAGEMENT? - Yahaya, Jahara; Santha, Chenayah (Malaysian Journal of Science, 2004)
In Malaysia, there are working plans for the conservation and management of mangroves in Matang, Perak. Pioneered by the British Administration, the Matang mangroves exemplify an example of sustainable use for timber production and fishery production without compromising the ecological and environmental values of the ecosystem. Thus, management of mangrove forests inherently involves multiple criteria approach for ranking alternatives for its sustainable use. The purpose of this study is to investigate the need for sustainable mangrove forest management in Malaysia. In this paper, first, we discuss the issues involved in proper management of mangroves in Malaysia. Subsequently, we examine the formulation of a sustainable mangrove management plan. We conclude with some recommendations for further considerations.